2018
DOI: 10.1080/02656736.2018.1506167
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the survival impact of dexmedetomidine in children undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy

Abstract: Objective: Recent evidence suggests the a2-adrenoreceptor agonist dexmedetomidine may promote metastasis of cancer cells. In this study we sought to evaluate the impact of dexmedetomidine administration on the survival of children and adolescents with cancer. Design: Retrospective chart review. Setting: Comprehensive cancer center. Patients: Children and adolescents who had undergone cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for peritoneal carcinomatosis. Intervention: Intraoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The median intraoperative administered doses of dexmedetomidine in the two previous trials on patients with lung cancer were 100 μg (57.47–140 μg) [ 16 ] and 122 μg (118–146 μg) [ 17 ], both of which are higher doses than that used in this study. Pascal et al, who reported findings that were consistent with our findings, used a dose of 0.1–0.7 μg/kg/h [ 19 ]. These inconsistent findings further indicate a mixed survival effect of low-dose dexmedetomidine.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The median intraoperative administered doses of dexmedetomidine in the two previous trials on patients with lung cancer were 100 μg (57.47–140 μg) [ 16 ] and 122 μg (118–146 μg) [ 17 ], both of which are higher doses than that used in this study. Pascal et al, who reported findings that were consistent with our findings, used a dose of 0.1–0.7 μg/kg/h [ 19 ]. These inconsistent findings further indicate a mixed survival effect of low-dose dexmedetomidine.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the data of the previous randomized controlled trials [ 19 , 20 ], this study showed that dexmedetomidine did not significantly affect BCR and radiographic progression in patients with prostate cancer within 4–6 years after RALP. Previous findings regarding this topic have been inconsistent, and the effect of dexmedetomidine on prostate cancer cell lines remains unclear.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The dissemination of cancer cells from primary tumors and subsequent seeding of new tumor colonies in distant tissues involves a multistep process known as the invasion-metastasis cascade, in which the Src system seems to play an important role [42]. Lidocaine at clinically achievable concentrations has been shown in vitro to statistically inhibit the phosphorylation of Src and the ICAM-1 expression in human lung cancer cells [43]. This study also demonstrated that the effect was independent of the function of the sodium ion channel.…”
Section: Update On the Available Evidence Regarding Anesthetic/anamentioning
confidence: 99%